2012
DOI: 10.1002/jcu.21988
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic diagnosis and monitoring of localized langerhans cell histiocytosis of the skull

Abstract: The US appearance of focal LCH lesions in cranial bones in children is not pathognomonic, but is characteristic enough to suggest an initial diagnosis and to monitor the evolution of lesions during treatment. US should be considered an additional diagnostic tool for LCH of the skull. Although US of localized LCH cannot replace CT, it could reduce the number of follow-up CT examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
7
0
2
Order By: Relevance
“…The point‐of‐care focused skull US findings in both of our cases showed the typical US appearance of Langerhans cell histiocytosis skull lesions as described in the literature previously, which is a focal well‐demarcated oval or round lesion of very low echogenicity (almost anechoic) with evident destruction of the adjacent bone 5 . Adjacent soft tissue thickening and disorganized vascularity at the periphery and in the center were also noted by Kosiak et al 5 in larger lesions (>20 mm).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The point‐of‐care focused skull US findings in both of our cases showed the typical US appearance of Langerhans cell histiocytosis skull lesions as described in the literature previously, which is a focal well‐demarcated oval or round lesion of very low echogenicity (almost anechoic) with evident destruction of the adjacent bone 5 . Adjacent soft tissue thickening and disorganized vascularity at the periphery and in the center were also noted by Kosiak et al 5 in larger lesions (>20 mm).…”
Section: Discussionsupporting
confidence: 81%
“…The role of US in the diagnosis of Langerhans cell histiocytosis to date has been limited to the evaluation of hepatic and splenic lesions in multisystem disease. Kosiak et al 5 assessed 27 patients with localized Langerhans cell histiocytosis of the skull and found that all lesions visible on CT were also visualized by US imaging performed by radiologists. It has been suggested that the US appearance of focal Langerhans cell histiocytosis lesions of the skull in children is sufficiently characteristic to suggest an initial diagnosis and could also be used to monitor treatment 5 …”
Section: Discussionmentioning
confidence: 99%
“…The most important imaging for LCH patient assessment is ultrasonography. The use of a new imaging technique called static elastography for assessment of changes in the skull and other bones allows for more complete differential diagnoses because the typical images reveal hyperplastic (hard changes) and fluid changes (rainbow artefact or the artefact buffalo eye) in unicameral bone cysts ( Figures 1 , 2 ) [ 93 ].…”
Section: Recent Advances In Imaging Evaluationmentioning
confidence: 99%
“…However, the absence of deep tumor margin on the transverse views, a finding that is usually present in osteolytic lesion limited to the cortex, may suggest that the mass occupies the entire medullar cavity. Kosiak et al showed recently that in cases of histiocytosis of the skull, US was a modality of choice in the evaluation of superficial lytic bone lesions. Like long bones, ribs and skull are frequent sites of MM and US could represent an additional imaging modality, especially for guiding biopsy or monitoring the lesion under treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Kosiak et al showed recently that in cases of histiocytosis of the skull, US was a modality of choice in the evaluation of superficial lytic bone lesions. Like long bones, ribs and skull are frequent sites of MM and US could represent an additional imaging modality, especially for guiding biopsy or monitoring the lesion under treatment . Further investigations in a large population are required to evaluate prospectively the role of US in MM.…”
Section: Discussionmentioning
confidence: 99%